Study of Structure and Spectral Characteristics of the Zinc(II) and Copper(II) Complexes With 5,5-Dimethyl-2-(2-(3-nitrophenyl) hydrazono)cyclohexane-1,3-dione and Their Effects on Optical Properties and the Developing of the Energy Band Gap and Investigation of Antibacterial Activity - Turan, Nevin; Gündüz, Bayram; Korkoca, Hanifi; Adiguzel, Ragip; Colak, Naki; Buldurun, Kenan (SOC QUIMICA MEXICO, 2014)
A new chelating ligand, 5,5-dimethyl-2-(2-(3-nitrophenyl)hydrazono)cyclohexane-1,3-dione (L), and four transition metal complexes were synthesized. The ligand and its complexes were characterized by IR, H-1 and C-13-NMR spectra, elemental analyses, magnetic susceptibility, mass spectra, UV-Vis. and thermogravimetry-differential thermal analysis (TGA-DTA). The metal complexes showed different geometric structures. Antibacterial tests of the ligand and complexes were also done. The Zn(II) complexes showed antibacterial activity against Staphylococcus aureus ATCC-25923 at middle level. The optical properties of the ligand and its complexes were extensively investigated by optical measurements. The average transmittance value of the ligand was the highest value, while the average transmittance value of the [CuL2(NO3)(2)]center dot 6H(2)O complex was the lowest value. The optical band gap of the ligand, [(Zn)(2)L(OH)(4)]center dot 2DMF, [ZnL(NO3)(2)(H2O)(2)]center dot 5H(2)O, [CuL2(OAc)]center dot OAc center dot 3.5H(2)O and [CuL2(NO3)(2)]center dot 6H(2)O complexes were calculated and 3.121 eV, 2.180 eV, 1.551 eV, 2.489 eV and 1.556 eV values were found, respectively. The complexes decreased the optical band gap of the ligand. The optical band gap value of the [ZnL(NO3)(2)(H2O)(2)]center dot 5H(2)O complex is the lowest value. The optical band gap value of the ligand is the highest value. The complexes decrease the angle of incidence of the ligand, while complexes increase the angle of refraction of the ligand. The electric susceptibility of the ligand decreases with its complexes.
Keywords: Characterization; hydrazono; antibacterial activity; optical properties; energy band gap; metal complexes